Proyecto de creación de un centro de rehabilitación y terapia física integral - Rubio, G. (2010)
The project is located in a local context, specifically in the city of Guayaquil, led to two segments: people with temporary physical disabilities, be they due to illness, accident, old age or physical rehabilitation for athletes, is also intended for people with evergreen or semi-permanent physical disabilities, who need to perform ongoing physical therapy in order to become active members of society. This project, by its nature of "private" is exclusively aimed at people of middle class, upper middle and high. With Integrated Medical Center, patients can find in the city of Guayaquil a complex rehabilitation therapist where they can optimally and efficiently. Specifying the various existing types of physical therapy, consider the main problem to solve. Its main objective is to develop a Center for Comprehensive Rehabilitation and Physical Therapy in the city of Guayaquil that meets in a personalized way for people who need it, with highly trained professionals by German doctors. To differentiate ourselves from the competition today, will be offered high quality, leveraging the expertise of renowned German therapists who have successfully implemented various types of physical therapy to which their patients have responded favorably, with supplementary use of special machines the latest technology. Building a big boost with marketing and our extensive experience in the treatment field will have great success with the project IBPGR.